Strong flux pinning enhancement in YBa2Cu3O7-x films by embedded BaZrO3 and BaTiO3 nanoparticles - 丁发柱 古宏伟 张 腾 王洪艳 屈 飞 邱清泉 戴少涛 彭星煜 (中国物理B：英文版, 2013)
YBa2Cu3O7-x （YBCO） films with embedded BaZrO3 and BaTiO3 nanoparticles were fabricated by metalorganic deposition using trifluoroacetates （TFA-MOD）. Both X-ray diffraction and transmission electron microscopy revealed that these BaZrO3 and BaTiO3 nanoparticles had random orientations and were distributed stochastically in the YBCO matrix. The unique combined microstructure enhances the critical current density （Jc） of the BaZrO3/BaTiO3 doped-YBCO films, while keeping the critical transition temperature （Tc） close to that in the pure YBCO films. These results indicate that BaZrO3 and BaTiO3 nanoparticles provide strong flux pinning in YBCO films.